Development of biomedical Ti-Nb-Zr-Mn alloys with enhanced mechanical properties and corrosion resistance. (March 2022) - Wu, Jiang; Tan, Xiao; An, Xuguang; Zhang, Jing; Guo, Yi; Liu, Jia; Luo, Yuanqi; Yao, Weitang; Kong, Qingquan; Wang, Qingyuan
Abstract: In order to develop a new biomedical titanium alloy with excellent mechanical properties and corrosion resistance, a series of newly designed Ti-24Nb-4Zr-xMn (x = 0, 1, 3, 5 wt%) alloys based on Mo equivalent method and d-electron alloy design theory were successfully fabricated by mechanical alloying and spark plasma sintering. The effect of Mn content on the microstructures, mechanical properties and corrosion resistance of the Ti-Nb-Zr-Mn alloys were systematically investigated. The results showed that moderate Mn is beneficial to the formation of the fine and uniform α'' and β grain, which is helpful to improve the mechanical properties. Among all the investigated alloys, Ti-24Nb-4Zr-3Mn alloy prepared under 40 MPa (TNZ3M-40) exhibited the highest compressive strength (2336 MPa) and large strain ( 35%). In addition, the electrochemical measurements showed that the addition of Mn can further improve the corrosion resistance, and the corrosion potential and corrosion current density in Ringer's solution are − 0.207 V and 27.28 nA/cm 2 for TNZ3M-40, respectively. This study offers a potential strategy for developing biomedical Ti-Nb-Zr-Mn alloys with high performance for biological implantation.